Diseño de un sistema de bombeo eficiente utilizando energía solar. - Torres Cueva, Edwin Leonardo (2004)
In this work a system of pumping of water is designed for the agriculture and for a community using photovoltaic energy. This work is framed inside the actions of the community of Loja guided to the exploitation of the non-conventional energy with the objective of conserving the environment, to use the own natural resources and to achieve certain independence regarding the conventional sources of energy.